Standard germination test in physic nut (Jatropha curcas L.) seeds - Oliveira,Glauter Lima (2014)
Defining adequate methods to assess seed germination is important to control the quality of commercial lots, especially for species that are not yet included in the Rules for Seed Testing. This study aimed to establish an adequate procedure for germination test in physic nut seeds (J. curcas L.). Three seed lots, in eight replications of 25 seeds each, were sown on paper towel rolls moistened with a water volume equivalent to 2.7 the weight of the dry paper and in sterilized sand moistened up to 60% of its water-holding capacity. The seeds of each treatment were maintained on germination chambers at temperatures of 20, 25, 30 and 20-30 ºC. Daily counts were made to define the ideal date to perform the first and the last count test. Criteria for classifying seedlings as normal and abnormal were also established. The experiment was conducted in a completely randomized design in a split plot arrangement, and the means were compared by Tukey's test (P<0.05). For maximum germination potential of physic nut seeds, the germination test should be conducted at 25 ºC and 30 ºC, using sand or paper towel as a substrate, with the counts at 7 and 12 days after sowing.